Mechanical Properties of Az91 Magnesium Alloys - Pavel Lukac; Zuzanka Trojanova (Communications - Scientific letters of the University of Zilina, 2004)
Commercial magnesium alloys AZ91 were reinforced with Al2O3 short fibres. The composites were prepared by different fabrication routs (powder metallurgy technique, squeeze casting and casting followed by extrusion). Some specimens of the AZ91 alloy were prepared using equal channel angular pressing. The values of the yield stress and the maximum stress of specimens deformed at temperatures between 20 and 300 °C were determined. The test temperature strongly influences the mechanical properties of the AZ91 alloy and its composites.